Personal values prioritized by the Adventist professionals in Peru - Niño de Guzmán, Juan Carlos (2016)
The purpose of this research is to describe the personal values that are prioritized by the Adventist professionals in Peru. Research has an experimental design and is not cross. For data collection Personal Values Survey in a sample of 250 Adventist professionals distributed in Peruvian territory it was applied. In addition, the questionnaire was presented to Adventist professionals located near the three campuses (Lima, Juliaca and Tarapoto) of the Peruvian Union University. The survey measures four dimensions of personal values: Achievement search, search Placer, honesty and respect. The results show that the personal values more prioritized by the Adventist professionals are in the dimension of Honesty; to demonstrate that a confirmatory factor analysis was performed, the same as identified two marked groups in the sample, of “postmodernist Identity” and those of “Adventist Identity”, the latter have a behavior more conservative and have very internalized values sincerity, trust, integrity, harmony, reciprocity, responsibility, honor, esteem, tolerance, appreciation, perseverance, among others. In conclusion, personal values practiced with greater prominence, by Adventist professionals are honesty and the Pursuit of Achievement; however, worth noting that Respect is one of the values that need to be improved, and that there is a segment of Adventist professionals who have a tendency to prioritize pleasure.